Sistem Pemerintahan Indonesia Pasca Reformasi (Perubahan Konstitusional UUD 1945) - Wilma Silalahi; Agusman (PT PUSTAKA CENDEKIA GROUP, 2025)
The 1998 Reform marked a crucial milestone in Indonesia’s democratic development, leading to constitutional amendments that reshaped the state system. The 1945 Constitution initially positioned the People’s Consultative Assembly (MPR) as the highest state body with the authority to elect the President without term limits, a structure considered incompatible with modern democratic principles. Through four constitutional amendments (1999–2002), significant changes were introduced, including direct presidential elections, a two-term presidential limit, the repositioning of the MPR, the strengthening of the DPR, the establishment of the Regional Representative Council (DPD), the Constitutional Court, and the Judicial Commission. These reforms consolidated the presidential system, reinforced the checks and balances mechanism, and improved democratic quality. Nevertheless, post-reform political practice still faces challenges such as the dominance of political parties, limited legislative authority of the DPD, and coalition politics that often resemble a parliamentary system. This study aims to analyze Indonesia’s system of government after the constitutional amendments using a normative-juridical approach.